Labour-use efficiency in Tunisian manufacturing industries: A flexible adjustment model - Ilham Haouas; Mahmoud Yagoubi; Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper investigates the process of adjustment in employment. A dynamic model is applied to a panel of six Tunisian manufacturing industries observed over the period 1971–96. The adjustment process is industry and time specific. The adjustment parameter is specified in terms of factors affecting the speed of adjustment. Industries are assumed to adjust their labour inputs towards a desired level of labour-use. A translog labour requirement function is specified in terms of observable variables and is used to model the desired level of labour-use. The labour requirement is specified to be function of wages, output, quasi-fixed capital stock and technology. The empirical results show that in the long-run, employment demand responds greatest to value-added, followed by capital stock changes, and least by wages. The speed of adjustment in employment and the degree of labour-use efficiency show large variations among the sectors and over time. – dynamics ; employment ; labour-use efficiency ; panel data ; Tunisia ; speed of adjustment ; technical change
Keywords: C23; E24; J33; L60; 330; Verarbeitendes Gewerbe; Beschäftigung; Arbeitsnachfrage; Tunesien